2011
DOI: 10.1097/maj.0b013e31821aa000
|View full text |Cite
|
Sign up to set email alerts
|

Progress Toward Improving Animal Models for Idiopathic Pulmonary Fibrosis

Abstract: Idiopathic pulmonary fibrosis (IPF) remains a disease with an unknown cause and a poor prognosis. Among attempts to define disease pathogenesis, animal models of experimental lung fibrosis have a prominent role. Commonly employed models include exposure to bleomycin, silica, fluorescein isothiocyanate; irradiation; or expression of specific genes through a viral vector or transgenic system. These have all been instrumental in the study of lung fibrosis, but all have limitations and fall short of recapitulating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
132
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(135 citation statements)
references
References 30 publications
1
132
0
2
Order By: Relevance
“…Our recent genetic lineage-tracing studies in the mouse clearly established that SFTPC + AEC2s, as a population, proliferate in vivo and give rise to AEC1s (13). These data also showed that these processes, which are normally quite slow, are stimulated after injury with bleomycin, a chemotherapeutic agent that damages multiple cell types in the alveoli and induces transient inflammation and fibrosis (14).…”
Section: Introductionmentioning
confidence: 66%
“…Our recent genetic lineage-tracing studies in the mouse clearly established that SFTPC + AEC2s, as a population, proliferate in vivo and give rise to AEC1s (13). These data also showed that these processes, which are normally quite slow, are stimulated after injury with bleomycin, a chemotherapeutic agent that damages multiple cell types in the alveoli and induces transient inflammation and fibrosis (14).…”
Section: Introductionmentioning
confidence: 66%
“…This model typically involves either repetitive s.c. injection of bleomycin or a one-time intratracheal injection of the drug (22). The former method has been criticized for its inability to separate antiinflammatory from antifibrotic effects, whereas the latter method frequently suffers from high interanimal variability in inducing fibrotic disease (21,23). To separate the inflammatory phase of this model from the subsequent fibrotic stages, we chose to administer bleomycin (25 mg/kg) via a subdermally implanted osmotic pump for 7 d, after which time the pump was surgically removed, and mice were left untreated for 7 d for inflammation to subside and fibrotic progression to begin (SI Appendix, Fig.…”
Section: Significancementioning
confidence: 99%
“…bleomycin-induced lung fibrosis model. Despite some inherent limitations in modeling the human disease, both clinically approved antifibrotic drugs have shown efficacy in the bleomycin mouse model (14,20,21). This model typically involves either repetitive s.c. injection of bleomycin or a one-time intratracheal injection of the drug (22).…”
Section: Significancementioning
confidence: 99%
“…Therefore, we employed C57BL/6 background mice with bleomycin in the dose, in which the administration did not cause lethality in wild-type mice. 36,39 Although BALB/c background wild-type and periostin-null mice displayed the same survival rate (about 90%) at the acute phase in the bleomycin administration, 6 we found that C57BL/6 background periostin-null mice exhibited higher lethality than their wild-type counterparts in the case of 2.5 U/kg bleomycin administration. Taken together, our study suggests that periostin strengthens the ECM structure of intact alveolar wall and acts in a protective manner during ALI.…”
Section: Discussionmentioning
confidence: 82%